2017
DOI: 10.1097/ta.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

Novel oral anticoagulants and trauma

Abstract: Prognostic/epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 42 publications
4
46
0
1
Order By: Relevance
“…The univariate and multivariate analyses did not reveal any higher risk for ICH and progression of intracranial bleeding in patients on DOACs compared to VKAs (19% in each group). Interestingly, this study discovered that aspirin intake was associated with the highest rate of ICH diagnosed upon admission [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The univariate and multivariate analyses did not reveal any higher risk for ICH and progression of intracranial bleeding in patients on DOACs compared to VKAs (19% in each group). Interestingly, this study discovered that aspirin intake was associated with the highest rate of ICH diagnosed upon admission [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to the report of Wood et al, where 60% of patients on VKA and only 19% of DOAC patients received reversal agents [ 13 ]. In a multicentre study published by Kobayashi et al, the anticoagulant effect of warfarin was reversed in only 47% compared with 13% of the DOAC patients ( p < 0.001) [ 24 ]. Barletta et al reported similar rates of pharmacological reversal (48.1% [warfarin] vs. 13.8% [DOAC], p > 0.001) but, despite this, mortality was comparable between warfarin and DOAC patients (5.9% vs. 4.3%, p = 0.789) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of these DOACs in the trauma population has recently been assessed. DOACs have a considerably lower rate of the development of intracranial hemorrhage compared to warfarin (24% vs. 31%) [ 33 ]. While there has likely been benefit, the DOACs have few established protocols for reversal of anticoagulation, although work continues to be done in this area [ 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data previously presented. 22 For Renal Failure and Cirrhosis both the number of patients as well as percent (in parentheses) of the population with the comorbidity are presented. Values in bold signify number of patients and percent of population in parentheses.…”
Section: Resultsmentioning
confidence: 99%
“…Data used for this study were collected during a prospective observational study occurring between June 30, 2013 and July 1, 2015 across 16 level 1 trauma centers via the American Association for the Surgery of Trauma-Multi-institutional Trials Committee (AAST-MITC). 22 This is a post-hoc analysis of patients admitted on dabigatran, rivaroxaban, or apixaban. Minors (age <18), patients who were pregnant, and prisoners were excluded.…”
Section: Methodsmentioning
confidence: 99%